Accelerating anaerobic propionate degradation and studying microbial community using modified polyvinyl alcohol beads during anaerobic digestion. (February 2022) - Sitthi, Sitthakarn; Hatamoto, Masashi; Watari, Takahiro; Yamaguchi, Takashi
Abstract: Modified polyvinyl alcohol beads (PVA) are synthesized by adding conductive materials such as activated carbon (AC), magnetite particles (MT), and green tuff (GT) for serving as potential advantages carriers on anaerobic digestion (AD). This study aimed to study the effect of modified PVA beads on AD performance and investigate the probability of DIET occurrence on syntrophic propionate degradation, including microbial syntrophy of syntrophic partners and methanogens. Under anaerobic sequencing batch reactor (ASBR) operation, chemical oxygen demand (COD) degradation was 1.3-fold higher, and propionate degradation increased 1.7-fold more than sludge. Another on the continuous stirred-tank reactor (CSTR), the COD degradation reached a maximum rate of over 80%, and propionate was completely degraded. Moreover, modified PVA beads were significantly promoted by methane production, methane conversion rate, and methane yield. The microbial syntrophy of " Candidatus Methanofastidiosum" and Syntophobacter co-occurred in modified PVA beads, illustrating the potential of syntrophic partner for propionate degradation. Graphical Abstract: Unlabelled Image Highlights: Modified PVA beads were successfully verified for a microbe carrier. Methane production was enhanced with modified PVA beads supplement. Syntrophic propionate-oxidizing bacteria and methanogen were enriched.